Maternal Age and Risk of Pregnancy Complications: A Qualitative Study - Nanda, Kiki Riskianti (Advances in Healthcare Research, 2025)
Purpose: This study aims to explore the relationship between advanced maternal age (≥35 years) and the risk of pregnancy complications through a qualitative perspective, emphasizing women's perceptions, experiences, and coping strategies. Research Method: A systematic literature review methodology was employed to synthesize qualitative research findings related to advanced maternal age and pregnancy complications. Relevant studies were reviewed to identify recurring themes, contradictions, and contextual gaps. Results and Discussion: The findings reveal that advanced maternal age is associated with heightened risks of complications such as preeclampsia, gestational diabetes, hypertension, preterm birth, and postpartum hemorrhage. Personal experiences, cultural beliefs, and access to healthcare influence perceptions of these risks. Women with higher perceived susceptibility are more likely to seek medical intervention, while those facing socio-economic barriers or cultural stigma exhibit lower health-seeking behaviors. Implications: The study underscores the importance of developing culturally sensitive maternal health programs tailored to the needs of older pregnant women. Healthcare providers should adopt empathetic communication strategies and accessible education programs. Future research should address this study's limitations by employing mixed-methods approaches and considering broader social determinants of health.